Engineering fundamentals an introduction to engineering - Moaveni, Saeed (Cengage Learning, 2016)
Now in dynamic full color, this Fifth Edition of SI ENGINEERING FUNDAMENTALS: AN INTRODUCTION TO ENGINEERING helps students develop the strong problem-solving skills and solid foundation in fundamental principles they will need to become analytical, detail-oriented, and creative engineers. The book opens with an overview of what engineers do, an inside glimpse of the various areas of specialization, and a straightforward look at what it takes to succeed. It then covers the basic physical concepts and laws that students will encounter on the job. To tie these principles to professional engineering, the author includes Professional Profiles that highlight the work of practicing engineers from around the globe. Using a flexible, modular format, the Fifth Edition demonstrates how engineers apply physical and chemical laws and principles, as well as mathematics, to design, test, and supervise the production of millions of parts, products, and services that people use every day.